Comparison of the ability of fifteen onion (Allium cepa L.) cultivars to accumulate nitrates - Renata Wojciechowska (Acta Agrobotanica, 2014)
The aim of a two-year study was to characterise selected Allium cepa L. genotypes with regard to their ability to accumulate nitrates in bulbs as well as to search for a possible relation between NO3- concentration and dry matter content. Fifteen cultivars of edible onion, mostly of long-day genotype with different growing periods, bulb size and skin colour, were taken for the experiment. Seeds of particular cultivars were obtained from the following seed companies: Spójnia Nochowo (‘Labrador’, ‘Takstar F1’,‘Tęcza’, ‘Warna’, ‘Zorza’), Polan (‘Polanowska’, ‘Topolska’), PlantiCo Gołębiew (‘Alibaba’, ‘Efekt’, ‘Kristine’, ‘Niagara F1’),and PlantiCo Zielonki (‘Bila’, ‘Irka’, ‘Wenta’, ‘Zeta’). Plants produced from seedlings were grown in the experimental field of the University of Agriculture in Kraków. After crop harvesting and additional drying, nitrate and dry matter content in bulbs of all cultivars were measured.